Development and validation of a computer expertise questionnaire for older adults. - Arning K; Ziefle M (Behaviour & Information Technology)
Prior computer expertise represents one of the most important predictors of performance when interacting with ICT (Information and Communication Technologies) and acquiring computer skills. Due to demographic changes, the older adult will become increasingly important as a potential user. However, there is a lack of instruments for the assessment of computer expertise in older adults, especially for novice users with restricted prior computer knowledge. A computer expertise (CE) questionnaire for older adults was developed, analysed (Study I) and validated (Study II). Item-analysis showed that the CE-questionnaire is particularly appropriate for the computer knowledge level of older adults and measures computer expertise sufficiently. Furthermore, it was found that computer experience (in terms of frequency of computer usage) is a poor predictor of actual computer performance, which has important implications for the theoretical conceptualization of computer expertise and its assessment.